Seasonal assemblages of epigean arthropods in a quebracho forest (Schinopsis balansae) in the Humid Chaco - MONTERO, GUILLERMO A.; CARNEVALE, NÉLIDA J.; MAGRA, GUSTAVO (Revista Colombiana de Entomología, 2011)
Chaco forests have high structural and floristic diversity, due to their soil conditions, their fire regimes and the intense logging that they have undergone. Arthropods can be good indicators of habitat heterogeneity, ecosystem biodiversity, as well as the stress of the environment. We carried out a taxonomic and a functional description of the epigeal arthropod assemblages of the soil surface in a quebracho forest. Samples were taken in convex areas with bromeliads (EB) and in flat areas with grasses (PS). Pitfall traps were used to capture arthropods for five consecutive days in three seasons (spring, summer and winter). In spring, we evaluated different physical and chemical characteristics of soil and litter. We captured 1668 individuals from 78 morphospecies; the ants are the most abundant taxa and the Coleoptera had the largest species richness. Lycosidae spiders were the most abundant spiders and Carabidae and Scarabaeidae presented the highest abundance among the Coleoptera. The species composition, trophic structure of epigeal arthropods and ant functional groups differed among seasons and between microsites. The higher ash content and conductivity in microsites EB is attributed to the contribution of shrubs leaves, which are rich in calcium, magnesium and potassium. The physical and chemical conditions of the litter-soil interface could determine the presence or abundance of detritivorous species at different microsites, accelerating the processes of litter decomposition.